An Eco-Cruise Control for Electric Vehicles Moving on Slope Road with Constant Speed. (18th October 2021) - Zhang, Ying; Zhang, Yingjie; Liu, Zhaohua; Chen, Jinchao; You, Tao; Du, Chenglie
Abstract : The unreasonable actuation of electric vehicle's motor drive system usually results in a lot of unwanted energy consumption on a slope road. This paper proposes an eco-cruise control (ECC) scheme based on the driving condition estimation to decrease electric vehicle's energy consumption in the constant-speed cruise control mode. The eco-cruise control scheme is realized by reducing the unreasonable actuation of the motor drive system. The vehicle's total mass and pitch angle are estimated in real time by using an improved base-vector-based cross iteration estimator (BVCIE). Based on the estimated results, the required torque is predicted. Combining the speed deviation between the desired speed and the real speed, and the torque deviation between the required torque and the real torque, a three-power nonlinear controller of the ECC scheme is designed. The ECC scheme is validated on a slope road with different cruise speeds on a cosimulation platform, and the results indicate that the proposed strategy enjoys a better speed maintenance ability and energy efficiency compared with the benchmarked cruise control.